Editorial - International Journal of Sustainable Energy Planning and Management Vol 17 - Østergaard, Poul Alberg (International Journal of Sustainable Energy Planning and Management, 2018)
This editorial introduces the 17th volume of the International Journal of Sustainable Energy Planning and Management. The volume present work on photo voltaic systems for decentralised applications and country studies of both Ghana, Kenya & South Africa and of Rwanda. Finally, methodology development papers on decision-making and biomass resource estimation round off the volume.